The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/cdep.12351
|View full text |Cite
|
Sign up to set email alerts
|

Stretching the Social: Broadening the Behavioral Indicators of Sociality

Abstract: Human infants are social by nature. Early behaviors taken as evidence of an innate desire to connect with others generally include eye contact, smiles, and positive vocalizations. Studies have shown that, as infants mature, they begin to alternate gaze between objects of interest and their social partners (joint attention), and show signs that some people are special to them by becoming distressed when separated from them (attachment). In this article, we seek to highlight less frequently studied ways that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The implications of our findings are particularly profound with regard to cross-cultural differences in infants’ everyday learning environments (Akhtar & Jaswal, 2020). Children across cultural contexts participate to highly variable extents in direct face-to-face interactions (e.g., Mesman et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The implications of our findings are particularly profound with regard to cross-cultural differences in infants’ everyday learning environments (Akhtar & Jaswal, 2020). Children across cultural contexts participate to highly variable extents in direct face-to-face interactions (e.g., Mesman et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…This finding adds to a growing body of research, which has showed altered mimicry of facial expressions presented to ASC participants on computer screens (Helt et al, 2020;Oberman et al, 2009;Senju et al, 2007) and of gestures performed during live interactions (Helt et al, 2010). Importantly, our interaction task was designed to be naturalistic, and yet, not biased towards NT interactions, which are characterised by coordinated exchanges such as mutual eye gaze and turn-taking (Akhtar & Jaswal, 2020). A naturalistic environment was attained for both ASC and NT participants by making the video as lifelike as possible and introducing the interaction task as a semi-structured memory game, while any potential experimenter bias and performance demands were eliminated through presenting the partner's actions via a pre-recorded video.…”
Section: Discussionmentioning
confidence: 83%
“…We would argue that these data are too often skewed by biased frames (of presumed incompetence) that distort and misrepresent individuals with CCN and exclude their perspectives. This argument is sustained by research that shows conventional measures for intelligence (e.g., WISC test batteries) generally underestimate the ability of nonspeaking autistics ( Courchesne et al, 2015 ; Nadar et al, 2016 ; Akhtar and Jaswal, 2019 ). When individuals with CCN, who were identified as having Intellectual Disability using language-based measures, were reassessed using more appropriate non-language-based instruments that employ visual spatial tasks, a significant proportion were found to be within or above the expected IQ range ( Dawson et al, 2007 ; Barbeau et al, 2013 ; Courchesne et al, 2015 ; Crossley and Zimmerman, 2019 ).…”
Section: Discussion: Presumption Of Communication Incompetencementioning
confidence: 99%